Visualisasi Tradisi Bedag-Bedagan Di Desa Adat Manukaya Let Tampaksiring Gianyar Bali Dalam Penciptaan Seni Lukis - Dalem Ramadi, I Gusti Ngurah; Tirta Ray, D. A.; Kondra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2021)
Bedag- Bedagan is a barong ket performance which the author adopted as the object of research in his final thesis entitled "Visualization of the Bedag- Bedagan Tradition in the Traditional Village of Manukaya Let Tampaksiring Gianyar Bali in the Creation of Painting." The aesthetic experience felt when watching the Bedag- Bedagan show was so impressive that the author felt, the barong ket performance with an interesting storyline, packed with unique character actions, using masks and classical dancer costumes reflecting local Balinese wisdom. In the process of pouring inspiration and creativity into the painting that the author creates, the author describes the Barong Ket object, which is combined with the objects of Bedag Bedagan as supporting objects according to the personal experience that the author feels while watching the Bedag Bedagan performance. There are several atmospheres that the author describes in the author's work regarding the Visualization of the Bedag- Bedagan Tradition in the Traditional Village of Manukaya Let Tampaksiring, Gianyar Bali in the Creation of this painting, which includes an emotional atmosphere, as well as a peaceful atmosphere at the end of the story. In the process of realizing the ideas in the six works, the author applies several stages including: the exploratory process, the experimental process, the manufacturing process, and the final stage is the completion process. The author includes elements of painting and aesthetic principles in the creation that the author visualizes into six works.